Possibilidades para a articulação entre teoria e prática em cursos de licenciatura - Dutra, Edna Falcão (2010)
This research was carried out inside Programa de Pós-Graduação em Educação of Centro de Educação from Universidade Federal de Santa Maria (UFSM), articulated to Research Project Dilemas e Perspectivas para a Inovação Educacional na Educação Básica e na Formação de Professores (DIPIED) and to Interventions, Researches and Studies Group Inovação Educacional, Práticas Educativas e Formação de Professores (INOVAEDUC) , between 2008 and 2010. With it, we sought to contribute to the studies, which aim to comprehend the proposed and developed theory and practice articulation ways in Teacher Education Courses (CL). For that, we proposed to answer to the following research problem: How occurs the relation between theoretical dimension and practical dimension in CL? The nature of the pieces of information collected as well the ways adopted for their treatment put your study into the qualitative researches set. The study dealt with 19 CL from UFSM. As information sources, we used, initially, two types of documents: 07 national legal orientations for teacher education to elementary and high school level and 19 Pedagogic Political Projects (PPP) of CL from UFSM. Furthermore, we had the contribution of 27 testimonials of professors from these Courses, directly engaged into activities or subjects that deal with, in a particular way, and/or provide, explicitly, the theoretical dimension and practical dimension articulation in teacher education. As instruments to collect information, we used a specific set of aspects to analyze the quoted documents as well a particular set of aspects for structured interviews accomplishment with the 27 selected professors. To analyze the pieces of information gotten, we applied, basically, some principles of the called Subject Analysis, in the perspective proposed by L. Bardin. From the gotten information treatment, we evidenced that the analyzed legal documents point out that theory and practice articulation must occur as into subjects which have hours devoted to Practice as Curricular Component, shared throughout the course, as into subjects referent to Pre-Service Curricular Training, which must begin from the second part of the course. For this set of subjects, it is prescribed at least 800 hours during the entire course, 400 hours for each curricular component mentioned. Nevertheless, these documents do not offer elements neither indicate ways of articulating theory and practice, pointing out just the time quantity definition. The introductory texts of almost all of the PPP from CL investigated (16/19) reaffirm the importance of articulating theory and practice in the teacher education, thus, in agreement with the documents analyzed. However, these PPP only make reference to the need of relating theory and practice, they do not present mechanisms for its development. The professors interviewed testimonials, allowed us to understand that the didactic activities carried out by them are partially in consonance with the prescribed in legal documents, as in the majority of professors of CL speeches (24/27), predominates the idea that practical activities serve just to apply the theories studied during the teacher education. The ideas manifested by them on theory and on practice constitute points of view that vary from a dichotomy position between these two reality dimensions to an articulation position between them. Yet, when asked for analyzing the situation of the current teacher education courses, they are almost unanimous (26/27) in believing that they are mostly based on a dichotomy view between these dimensions. More specifically, referring to the own courses in which they teach, still the majority (16/27) evaluate that such courses reaffirm this dichotomy. Nevertheless, when asked to reflect on their own teaching actions, the entirety (27/27) reports that seek always to develop a work providing articulation between theory and practice in future teacher education for basic levels. As conclusion, we mention different possible contributions for accomplishment of activities that improve the theory and practice articulation in teacher education processes: 1) development of the capacity of working with the called education transposition ; 2) knowledge of real work spaces still throughout the teacher initial education; 3) possibility of developing, in a school setting, a work different from the one they lived in the basic school; 4) stimulus for reflecting on the type of professionals they can be; 5) possibility of becoming a researcher teacher, that act, reflect and research on their own teaching practice.